POLA RELASI HUKUM INTERNASIONAL DAN NEGARA PADA PERUNDINGAN MASALAH PAPUA BARAT TAHUN 1950- 1962 - M Syaprin Zahidi; Hafid Adim Pradana (UNIDA Gontor, 2020)
This research is a new perspective on international relations research. This study tries to criticize the previous view that considers international law as a norm or principle that must be obeyed by the countries in this world. Yet in reality, international law can be used as an instrument by countries to achieve their respective national interests. Departing from the above statement, this research focuses on the process of negotiating the West Irian problem after the Round Table Conference agreement in 1949 until the New York Agreement in 1962 was signed between Indonesia and the Netherlands. Through observation of the negotiation process, this study seeks to see patterns of relations between international and state law, especially in the process of negotiating the West Papua issue which took place after the Round Table Conference (RTC) in 1949 until the New York Agreement in 1962. Using a qualitative descriptive approach as a research method, and the perspective of realism in international law as a theoretical framework, this research results in finding that there is a pattern in the relations of international and state law in the negotiations on the problems of West Papua in 1950-1962 which manifests in the form of utilizing international law as an instrument of achieving the interests of a country